Waiting and the Temporalities of Irregular Migration - Jacobsen, Christine M.; Karlsen, Marry-Anne; Khosravi, Shahram (Taylor & Francis, 2021)
"This edited volume approaches waiting both as a social phenomenon that proliferates in irregularised forms of migration and as an analytical perspective on migration processes and practices. Waiting as an analytical perspective offers new insights into the complex and shifting nature of processes of bordering, belonging, state power, exclusion and inclusion, and social relations in irregular migration. The chapters in this book address legal, bureaucratic, ethical, gendered, and affective dimensions of time and migration. A key concern is to develop more theoretically robust approaches to waiting in migration as constituted in and through multiple and relational temporalities. The chapters highlight how waiting is configured in specific legal, material, and socio-cultural situations, as well as how migrants encounter, incorporate, and resist temporal structures. This collection includes ethnographic and other empirically based material, as well as theorizing that cross-cut disciplinary boundaries. It will be relevant to scholars from anthropology and sociology, and others interested in temporalities, migration, borders, and power. "